Substantial Sub-Surface Chlorophyll Patch Sustained by Vertical Nutrient Fluxes in Fram Strait Observed With an Autonomous Underwater Vehicle - Tippenhauer, Sandra; Janout, Markus; Chouksey, Manita; Torres-Valdes, Sinhue; Fong, Allison; Wulff, Thorben (Frontiers in Marine Science, 2021)
We present results from a coordinated frontal survey in Fram Strait in summer 2016 using an autonomous underwater vehicle (AUV) combined with shipboard and zodiac-based hydrographic measurements. Based on satellite information, we identified a front between warm Atlantic Water and cold Polar Water. The AUV, equipped with oceanographic and biogeochemical sensors as well as a microstructure turbulence probe, then profiled the upper 50 m along a 10 km-long cross-frontal transect resulting in a high-resolution snapshot of the upper ocean. The transect was dominated by a 6 km wide, 10-m thick subsurface patch of high chlorophyll, located near the critical euphotic depth within a band of cold water. Nitrate was depleted in the surface, but abundant below the pycnocline. Microstructure temperature and Richardson number estimates indicate conditions favorable for vertical mixing, which indicates that the high chlorophyll patch may have been sustained by upward nitrate fluxes. Our observations underline the complex hydrographic and biogeochemical structure in a region featuring fronts and meanders, and further underline the patchy and small scale nature of subsurface phytoplankton blooms fueled by submesocale dynamics, which are easily missed by traditional surveys and satellite missions.